The Role of Anapanasati Meditation in Enhancing Mental and Emotional Health - Oktavani, Sucipta Erlingga; Lauw Acep (The Future of Education Journal, 2026)
Students’ mental health has increasingly declined due to the pressures of modern education, necessitating mindfulness-based interventions such as Anapanasati from the Buddhist tradition. This study aims to explore the role of Anapanasati in enhancing mental and emotional well-being. Employing a descriptive phenomenological qualitative approach, the population consisted of Anapanasati practitioners at Institut Nalanda, with three key informants selected through purposive sampling (Ko Maja, Ko Hendri, and Bu Metta). Data were collected through semi-structured interviews and analyzed using Moustakas’ phenomenological procedures, including epoche, horizontalization, and thematic analysis. The findings revealed four major themes: managing life stress, developing personal potential, improving academic and professional performance, and fostering social contribution. Anapanasati practice was found to cultivate self-awareness and enhance emotional regulation. The study concludes that Anapanasati is an effective holistic intervention within Buddhist religious education and is recommended for integration into school programs to promote students’ well-being.